Intellectual Property Marketplace: Increasing Information Technology-Based Public Sector Marketing in Indonesia - Nuralia, Nuralia; Imbaruddin, Amir; Utomo, Tri Widodo Wahyu; Suwarno, Yogi (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
The marketing of intellectual property outcomes holds paramount importance. This study examines the potential utility of the Intellectual Property Marketplace as a promotional instrument for the public sector, particularly in information technology. This study analysed pertinent literature and secondary data concerning the evolution of IP Marketplaces globally, focusing on Indonesia. Our findings reveal that the IP Marketplace established by the Ministry of Law and Human Rights has emerged as a novel platform for optimising the marketing of IP-generated products. This web-based IP Marketplace serves as a hub connecting intellectual property producers and potential clientele. A critical recommendation for further development entails formulating a regulatory framework to ensure that the convenience offered by the IP Marketplace does not compromise the security and authenticity of intellectual property products